The design of computer supported cooperative work and groupware systems - Shapiro, Dan S.; Tauber, Michael J.; Traunmuller, R. (Roland) (Amsterdam ; New York : Elsevier, 1996)
The phrases <Q>the information superhighway</Q> and the <Q>the information society</Q>are on almost everyone's lips. CSCW and groupware systems are the key to bringing those phrases to life. To an extent that would scarcely have been imaginable a few years ago, the contributions in this volume speak to each other and to a broader interdisciplinary context. The areas of ethnography and design, the requirements and principles of CSCW design, CSCW languages and environments, and the evaluation of CSCW systems are brought together, to bring to light how activities in working domains are really in practice, carried out. The aim above all is to do justice to the creativity and versatility of those whose work they aim to support.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Groupware (Computer software) -- Congresses; Computer software -- Development -- Congresses; Teams in the workplace -- Data processing -- Congresses; Human-computer interaction -- Congresses; System design -- Congresses; Electronic books